Differential vasoproliferative traits of Bartonella henselae strains associated with autotransporter BafA variants - Yuka Kondo; Masahiro Suzuki; Shingo Sato; Soichi Maruyama; Akiko Sei; Xingyan Ma; Kota Nakano; Yohei Doi; Kentaro Tsukamoto (Microbiology Spectrum)
ABSTRACT Bartonella henselae, a Gram-negative facultative intracellular bacterium, is the etiological agent of cat-scratch disease and also causes bacillary angiomatosis in immunocompromised individuals. Although the ability to promote vascular endothelial cell proliferation differs among Bartonella species, variations among strains within B. henselae remain unclear. Bartonella angiogenic factor A (BafA) and Bartonella adhesin A (BadA) have been identified as autotransporters of B. henselae that are involved in endothelial cell proliferation. Although strain-specific differences in the expression of BadA and the VirB/D4 type IV secretion system have been reported, BafA expression among B. henselae strains has yet to be examined. Therefore, the present study investigated the proliferation-promoting ability of 13 B. henselae strains from several sources in human umbilical vein endothelial cells (HUVECs). We identified BafA variants 1 and 2 based on the deduced amino acid sequences of its passenger domain. The recombinant proteins of both variants exhibited similar proliferation activity against HUVECs. However, BafA variant 2 strains showed cytotoxicity at a high bacterial inoculum in a direct coculture with HUVECs, which was attenuated in an indirect coculture. These strains, in contrast to BafA variant 1 strains, highly expressed BadA and exhibited bacterial aggregation. Based on a core genome SNP analysis of 50 B. henselae strains, the BafA variant types corresponded to clades 1–4. These results indicate that vasoproliferative traits differ among B. henselae clades based on the variant types. Therefore, this study provides a new conceptual framework in which the clades of B. henselae may predict their pathogenicity in humans.IMPORTANCEBartonella species including Bartonella henselae, Bartonella quintana, and Bartonella bacilliformis cause vasoproliferative lesions. Their proliferation-promoting ability in vascular endothelial cells differs among Bartonella species; however, it is unclear whether these differences exist among B. henselae strains. We herein showed that B. henselae strains exhibited variable proliferation-promoting ability and cytotoxicity in vascular endothelial cells, which corresponded to the bafA gene variants possessed by the strains. The expression levels of Bartonella angiogenic factor A (BafA) and Bartonella adhesin A, as well as the degree of proliferation-promoting ability and cytotoxicity in endothelial cells, varied among the strains. A core genome SNP analysis of strains using whole genome sequencing data divided B. henselae strains into four clades, with each clade corresponding to BafA variants 1–4. These results suggest the differential vasoproliferative potency of B. henselae, with potential implications in clinical management, including risk stratification and predictions of the clinical course.